Metalworking Technologies and Building Materials - Liang, Steven Y.; Watari, Hisaki; Abioye, Abiodun Ayodeji (Trans Tech Publications, 2024)
Special topic volume with invited peer-reviewed papers only.
Keywords: Metalworking industries.; elektronické knihy; electronic books